Front Cover: Selective Formation of Epoxylimonene Catalyzed by Phosphonyl/Arsonyl Derivatives of Trivacant Polyoxotungstates at Low Temperature (Eur. J. Inorg. Chem. 7/2020). Issue 7 (12th February 2020) - Makrygenni, Ourania; Vanmairis, Louise; Taourit, Sabrina; Launay, Franck; Shum Cheong Sing, Alain; Proust, Anna; Gérard, Hélène; Villanneau, Richard
Abstract : The Front Cover shows the oxidation of limonene to epoxylimonene with, in the background, orange trees typical of Réunion Island, where some of the studies reported in this manuscript have been carried out. Terpenes, especially limonene, are particularly present in citrus fruits, which constitute a part of the island's natural resources. The use of hybrid derivatives of polyoxometalates as effective catalysts from low temperatures allows their selective oxidation even within essential oils. More information can be found in the Full Paper by A. Shum Cheong Sing, R. Villanneau et al. For more on the story behind the cover research, see the Cover Profile.